Causes of differences in the uptake of cardiac implantation electronic devices in Slovenia in comparison to other countries - Prevolnik Rupel Valentina; Erker Renata; Divjak Marko (Sciendo, 2018)
The purpose of this study is to analyse and present the causes of the differences in crude utilization rate in cardiac implantation electronic devices, specifically pacemakers and automatic implantable cardioverter-defibrillators, across 5 European countries, with a specific emphasis on Slovenia.